Pharmacological and Toxicological Testing of the Enantiomers of two Chiral Fomocaine Alkylmorpholine Derivatives in Comparison to their in vitro Interactions on Drug Metabolism in Rats - Lupp, Amelie; Wange, Johannes; Oelschläger, Herbert; Fleck, Christian (Arzneimittelforschung, 2006)
Between the stereoisomers of amide-type local anaesthetics differences have been noticed with respect to pharmacokinetics and side effects, but not regarding local anaesthetic capacity. Therefore, only S-(-)-ropivacaine has been introduced into clinical practice and with bupivacaine both the racemate and the S-(-)-enantiomer (levobupivacaine) are available by now. Based on this background, the aim of the present study was to evaluate if there are also dissimilarities to be found both in the toxicity and in the effectiveness of the enantiomers of two newly synthesized chiral fomocaine alkylmorpholine derivatives, OW3 and OW13, with an additional C2-chain in 2- or an additional C3-chain in 3-position at the morpholine ring, respectively. For this purpose, in vitro the interaction capacity with cytochrome P450 (CYP)-mediated monooxygenase and oxidase functions was investigated using rat liver 9000 g supernatants or microsomes. In vivo LD50, paresis of the N. ischiadicus and surface and conduction anaesthesia (cornea, N. ischiadicus) were tested in rats.The enantiomers of both OW3 and OW13 caused a concentration dependent inhibition of all CYP-mediated model reactions investigated. With all model reactions the (-)-enantiomer of OW3 was less effective than the (+)-form, whereas the opposite was the case with OW13. Also toxicity was lower with the (-)-enantiomer of OW3 and with the (+)-form of OW13 than with the respective counterparts. With both derivatives no clear-cut dissimilarities were noticed in the local anaesthetic capacity of the enantiomers. None of the four compounds caused paresis.Thus, similar to amide-type local anaesthetics, also with the enantiomers of chiral fomocaine alkylmorpholine derivatives differences in pharmacokinetic properties and toxicity could be demonstrated.
Keywords: Alkylmorpholine; Cytochrome P450; Fomocaine, alkylmorpholine derivatives, enantiomers; Local anaesthetics, toxicity